The Effectiveness of Cupping Therapy in Reducing Blood Pressure in Hypertensive Patients at Citra Medika 3 Limau Manis Clinic - Herlina H; Sri Nur Yana; Chandra Pranata (Institut Kesehatan Medistra Lubuk Pakam, 2024)
Hypertension, a medical condition characterized by chronically elevated blood pressure, is one of the most prevalent cardiovascular diseases. Although asymptomatic in its early stages, hypertension can lead to serious complications in the cardiovascular system and other vital organs. Cupping therapy is a complementary treatment modality that has been used as an alternative approach to manage hypertension. This study aims to evaluate the effectiveness of wet cupping therapy in lowering blood pressure. The method employed involves the application of wet cupping therapy on patients with hypertension. The study results indicate that cupping therapy significantly lowers blood pressure in hypertensive patients, as evidenced by the Wilcoxon test showing a significant difference before and after the intervention. Based on the effectiveness of wet cupping therapy in lowering blood pressure, it shows potential for development as an alternative treatment for hypertension.